Les trames vertes : discours et/ou matérialité, quelles réalités ? - Laure Cormier; Nathalie Carcaud (Projets de Paysage)
The concept of Greenway is today present in many spatial planning orientation documents of France. In some cases, the greenway concept is use as a tool to take into account the ecological aspects of territories, with the creation of ecological corridors between “natural areas”. In other cases, the greenway concept refers to the planning strategy of creating open spaces in suburban areas with a sustainable development vision, i.e. taking into account their social, economic and environmental aspects. It now appears as an original approach of spatial planning, but we will see that this idea first emerged in United States at the end of the19th century. Then we will look at the application of this concept in planning documents at the European level, the national level, the regional level, the natural regional parks level and the agglomerations level. Finally, we discuss the effectiveness and the means used for the implementation of the greenway concept on the territory.